The Brazilian Legal System and Sustainable Development Goal (SDG 16): An Analysis for Achieving the Targets of the UN's Agenda 2030 - Júlio César Craveiro Devechi; Luiz Eduardo Gunther (Centro Universitário Adventista de São Paulo, 2023)
Objective: The objective of this research is to assess the effectiveness of the Brazilian legal system in facilitating the implementation and achievement of SDG 16 and its associated targets, in accordance with the Agenda 2030. Method: The study employs a comprehensive methodology that includes a thorough examination of the 17 Sustainable Development Goals articulated in the Agenda 2030. Specifically, SDG 16's overarching intention and its 12 universal targets are scrutinized in detail. Furthermore, relevant data collected by the Brazilian Supreme Court pertaining to this subject matter is presented and analyzed. Results: The paper provides critical reflections on the ethical and philosophical significance of SDG 16, drawing insights from renowned philosophers such as Axel Honneth, economist Amartya Sen, and Brazilian legal scholars Ricardo Sayeg and Wagner Balera. In addition, the study identifies and discusses key normative frameworks within the Brazilian legal system that can support the effective implementation of SDG 16's intention and universal targets in Brazilian society. Conclusion: Based on the analysis conducted, it is concluded that the existing Brazilian legislation has the potential to significantly contribute to the achievement of SDG 16 by 2030 if utilized effectively and conscientiously.